Qualitative and Quantitative Analysis on Some Cardiovascular Drugs - Gayathri, S.; Renuga Devi, T.S.; Gunasekaran, S. (Asian Journal of Chemistry, 2010)
In this present paper, qualitative and quantitative analysis were made on some cardiovascular drugs viz., amlodipine besylate, indapamide, atenolol and clopidogrel bisulphate by UV-Visible spectroscopy. The UV-Visible spectral recordings were carried out over ranges 200-400 nm. The stability of the drug under different environmental conditions is one of the quality assurance methods undertaken in the pharmaceutical laboratory. The UV-visible spectra have been recorded for the drug kept in suitable storage condition and for that exposed to various environmental hazards. The sets of internal standards of these drugs are compared with suitable storage conditions to check whether any change has taken place due to the exposure. The method of assay is experimented with these drugs using UV-visible spectroscopic measurements.